Isolation and characterization of a tobacco mosaic virus-inducible myb oncogene homolog from tobacco - Yang, Yinong (The National Academy of Sciences of the USA, 1996)
Salicylic acid (SA) plays an important role in signaling the activation of plant defense responses against pathogen attack including induction of pathogenesis-related (PR) proteins. To gain further insight into the SA-mediated signal transduction pathway, we have isolated and characterized a tobacco mosaic virus (TMV)-inducible myb oncogene homolog (myb1) from tobacco. The myb1 gene was induced upon TMV infection during both the hypersensitive response and development of systemic acquired resistance in the resistant tobacco cultivar following the rise of endogenous SA, but was not activated in the susceptible cultivar that fails to accumulate SA. The myb1 gene was also induced by incompatible bacterial pathogen Pseudomonas syringae pv. syringae during the hypersensitive response. Exogenous SA treatment rapidly (within 15 min) activated the expression of myb1 in both resistant and susceptible tobacco cultivars with the subsequent induction of PR genes occurring several hours later. Biologically active analogs of SA and 2,6-dichloroisonicotinic acid (a synthetic functional analog of SA), which induce PR genes and enhanced resistance, also activated the myb1 gene. In contrast, biologically inactive analogs were poor inducers of myb1 gene expression. Furthermore, the recombinant Myb1 protein was shown to specifically bind to a Myb-binding consensus sequence found in the promoter of the PR-1a gene. Taken together, these results suggest that the tobacco myb1 gene encodes a signaling component downstream of SA that may participate in transcriptional activation of PR genes and plant disease resistance.